An empirical study of factors influencing primary school teachers' long-term commitment to Realistic Mathematics Education - Nguyen, Giang Thi Chau; Pham, Chau Thi Hai (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2023)
Realistic Mathematics Education (RME) is a re-emerging teaching and learning pedagogy approach that has gained a lot of momentum since 2016. Prior publications concentrated mostly on curriculum design and student achievement, while little attention was devoted to understanding teachers’ perceptions toward RME. Thus, the purpose of this study was to investigate the effects of factors that influence teachers' perceptions to adopt RME in the long term. Ten hypotheses were proposed and tested employing the Generalized Structured Component Analysis (GSCA) technique. 226 primary school teachers from various regions were recruited to answer the questionnaires via Google Form. The experimental results validated six out of ten expected relationships between the factors in the extended self-determination theory model. That is, perceived competence affected confirmation, confirmation influenced both intrinsic motivation and satisfaction, intrinsic motivation influenced satisfaction, and satisfaction and parental involvement both were considered reliable predictors of realistic math education continuance intention. The remaining hypotheses were not validated, that is, autonomy, relatedness and competence were not found significant on intrinsic motivation, and intrinsic motivation did not influence RME continuance intention. Overall, the model explains 57.9% the amount of variance in the data. Administrators and policymakers are recommended to intervene on validated relationships to increase teachers' retention and long-term commitment to RME, whereas unsupported assumptions must be reexamined in the future.